Catalytic gas-phase hydrodeoxygenation of phenol over silica supported zinc catalysts at atmospheric pressure / Hamed Pourzolfaghar - Hamed , Pourzolfaghar (2021)
Hydrodeoxygenation (HDO) is a promising process for bio-oil upgrading derived from biomass wood. Although the result of the process performance is encouraging, further investigation still continues especially in obtaining the best type of catalyst in an atmospheric process condition. In this study, the HDO of phenol-based bio-oil catalyzed by Zn/SiO2 under atmospheric H2 pressure was investigated in a continuous fixed bed reactor. The physicochemical properties of the catalysts were surveyed by XRD, BET, ICP‐OES, EDX, H2-TPD, NH3‐TPD, TGA, H2-TPR, and FESEM. Following, the effects of various process parameters on the conversion efficiency and selectivity of the catalytic reaction products have been investigated. Finally, the stability and regenerability of the catalysts as well as the mechanism of the reaction have been surveyed. Characteristics outcomes indicated that the prepared catalyst is able to convert the phenol into aromatic hydrocarbons in low pressure hydrogen. The optimization study using various independent variables revealed that the hydrogen volumetric flow rate slightly affects product distribution and conversion efficiency. Process temperature increases the reaction conversion efficiency without changing the selectivity. The optimization study indicated that a process with 3% Zn/SiO2 as the catalyst, temperature at 500 ˚C, WHSV of 0.32 h-1, and H2 volumetric flow rate of 150 mL/min provides the highest possible conversion efficiency of phenol into aromatic hydrocarbons. The time-on-stream investigation illustrated that the silica-supported zinc was highly active up to 240 min of phenol HDO, with a conversion efficiency up to 80%, and after 420 min of TOS, the activity decreased to around a conversion rate of 43%. Reusability tests revealed that the catalyst displayed outstanding reusability and could be regenerated fully after four reusing rounds.